The law and economics of list price collusion - Willem Boshoff; Johannes Paha (Philipps-University Marburg, School of Business and Economics, 2017)
Firms sometimes violate competition laws by agreeing on increases of list prices. The economic effects of such list price collusion are far from clear because the cartel firms might deviate secretly from the elevated prices by granting their customers discounts. This article presents case evidence suggesting that agreements on list prices are not infrequently observed in cartel cases. It also reviews theoretical, empirical, and experimental literature in economics showing under what conditions such list price collusion causes the discounted transaction prices to rise. This is relevant for competition authorities in developing a theory of harm when prosecuting cartels, and also for the customers of the cartel firms when suing the conspirators for the repayment of damages.
Keywords: D43; K21; L41; 330